The Analysis of Mastering Main Idea in Narrative Text of Reading Question - Yusnida, Dara; Salaeh, Armeenoh; Rizka, Budi (Program Studi Pendidikan Bahasa Inggris, FKIP - Universitas Iskandar Muda, 2024)
This research aim to find out the students mastering main idea in reading text. Identification of main ideas are considered one of the basic skills in reading text and very important to be understood. The main of this research focuses on describing the student’s reading comprehension of narrative text. The population of this research were 14 students of the English Department at Iskandar Muda university. There were 4 students in semester II, 4 students in semester IV and 5 students in semester VI. In order to get the data, the researcher used the test. The total questions of the test were 20 items of multiple choices with 3 alternatives A, B and C about main idea in reading text. The data was analyzed by using descriptive method. The result showed that two students (14,29%) got very good level, four students (28,57%) got good level, four students (28,57%) got fairly good level, three student (21,42%) got weak level and one student (7,14%) got poor level. The mean percentage result of the students reading comprehension of narrative text in finding main idea was four students (28,57%) got good level and four students (28,57%) got fairly good level. It concluded that the English Department Students in finding main idea on reading comprehension text is categorized in good and fairly good. It is later suggested that future research would involve more about main idea in other university and find some problems there.